Syntactic Parallelism in the Nominal Sentence in the Zeni Maqamat - Amir Rafiq Awlla; Saad Saeed Majeed (Zanco Journal of Humanity Sciences, 2024)
This study is entitled: "Semantic Parallelism in the Zenian Maqamat" It aims to analyze the phenomenon of semantic parallelism in the Zenian Maqamat of Ibn al-Saqal al-Jazari (d.: 701 AH) linguistically to reveal the similarity based on a significant relationship, and synonymy, antagonism or opposition, and this important relationship is between two consecutive words or two words in one composition, or two successive combinations within one verbal chain, generating a musical rhythm originating from the resonance of the structure of words on the one hand, and from the meaning of words on the other hand. Art makes the text more harmonious. This research paper tries to reveal this phenomenon in the Zenian shrines, its nature, and how it is employed by the writer in a precise semantic manner that draws the attention of the recipient towards the text.